EVALUASI KERUSAKAN PERKERASAN JALAN RAYA BERBASIS WEB SERVICE MAPPING & SOLUSINYA - Ahmad Lutfi Manfaluti; Irawati Irawati; Daryanto Daryanto (HEXAGON, 2020)
On Jl. M. H. Thamrin with a length of 2.1 km and a width of 6.5 m with flexible pavement,there are various kinds of damage such as cracks, patches, depression, bleeding, and rutting along the road section. The evaluation of road damage condition is needed to monitor the level of damage that occurs. The method used in this condition survey is the Pavement Condition Index (PCI) method. This survey is intended to obtain the road pavement conditions based on the type, level extent of damage, and can be used as a reference in the road maintenance efforts, then analyzed using the Pavement Condition Index (PCI) Method.The survey results show the average type of damage percentage on the Jl. M. H. Thamrin Kec. Ajung Kab. Jember included: Alligator Cracks 45.11%, Longitudinal/ Transverse Cracks 18.5%, Patches 11.28%, Block Cracks 11.28%, Depression 0.75%, Bleeding 1.50%, Rutting 2.26% and 9.77% Edge Crack. Average PCI value on the Jl. M. H. Thamrin is 33% which is included inthe category of Very Poor. From the results of data processing of PCI, LHR, and CBR are sta 0 + 000 to 0 + 100, sta 0 + 100 to 0 + 200, sta 0 + 200 to 0 + 300, sta 0 + 400 s / d 0 + 500, sta 0 + 600 to 0 + 700, sta 0 + 900 to 1 + 000, sta 1 + 000 to 1 + 100, sta 1 + 200 to 1 + 300, sta 1 + 300 to 1 + 400, sta 1 +500 to 1 + 600, sta 1 + 800 to 1 + 900, sta 1 + 900 to 2 + 000, and sta 2 + 000 s / d 2 + 100 with recommendations for improvement used is the Local Patch with the Routine Maintenance Method of the 1995 Bina Marga Road.The damage is from 0 + 300 to 0 + 400, 0 + 500 to 0 + 600, 0 + 700 to 0 + 800, 0 + 800 to 0 + 900, 1 sta +100 to 1 + 200, sta 1 + 400 to 1 + 500, sta 1 + 600 to 1 + 700, and sta 1 + 700 to 1 + 800 The recommendations for improvement used is Overlay. Planning an additional layer (Overlay) with the 1987 Bina Marga Component Analysis Method with 7 cm result for an additional layer (Overlay) with Laston (MS. 590). From the database that has been obtained, integrates data into a database that has been created in SQLyog-64bit, and then enters the data attribute into QGIS Desktop 3.12.2 then enter to Pmapper, the last integrates into Web Service Mapping (Road Repair Decision Support System). It is make it easy to see each segment on the Jl.M. H. Thamrin Kec. Ajung Kab. Jember just click the point of damage in the map view will appear sta, the location of the damage, the level of damage, the length of the damage, the width of the damage, the depth of the damage, the extent of the damage, the width of the crack, the type of damage, documentation of the damage, and suggestions for repair.